The effects of aging on the cyclical thermal shock response of a copper-beryllium alloy as a substrate of cooling wheel in planar flow casting process - Deren Li; Zhichao Lu (Materials Research Express, 2020)
In planar flow casting (PFC) process, the molten alloy from nozzle exerts cyclical thermal shock on the substrate surface of cooling wheel and the cyclical thermal shock causes damage to the substrate surface in the form of defects. In this paper, a 2D numerical model was explored and the cyclical thermal shock on the surface of cooling wheel was simulated by numerical method using practical casting parameters. A batch of hot rolled copper-beryllium (Cu-2Be) cylindrical rings was prepared and subjected to solution annealing and aging treatments. The coefficients of thermal conductivity, thermal expansion coefficients and mechanical properties of Cu-2Be rings with different aging conditions were measured. The metallograph and SEM of the Cu-2Be rings subjected to 10 ^5 cycles of thermal shock were examined. The simulation results show that the surface temperature underneath the puddle is heated up drastically to a maximum temperature around 350 °C and cooled down to a minimum temperature around 140 °C in each revolution in quasi-steady process, and the lower thermal conductivity leads to the higher surface temperature for Cu-2Be substrate. The mechanical and physical responses of a Cu-2Be alloy aged at different conditions as a substrate of cooling wheel have been investigated after 10 ^5 cycles of thermal shock in practical casting. It was observed that the cyclical thermal shock leads to damage to Cu-2Be surface which affects the surface quality of as-cast ribbon. It was found that higher thermal expansion coefficient of Cu-2Be alloy leads to large magnitude of surface expansion and surface shrinkage which results in crack damage while lower thermal expansion coefficient of Cu-2Be alloy resulting from higher temperature aging is benefit to reducing the magnitude of surface expansion and surface shrinkage but the strength of Cu-2Be substrate is also reduced and intergranular erosion occurs after 10 ^5 cycles of thermal shock.